2020
DOI: 10.1371/journal.pone.0235823
|View full text |Cite
|
Sign up to set email alerts
|

Health management information system (HMIS) data verification: A case study in four districts in Rwanda

Abstract: Introduction Reliable Health Management and Information System (HMIS) data can be used with minimal cost to identify areas for improvement and to measure impact of healthcare delivery. However, variable HMIS data quality in low- and middle-income countries limits its value in monitoring, evaluation and research. We aimed to review the quality of Rwandan HMIS data for maternal and newborn health (MNH) based on consistency of HMIS reports with facility source documents. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
44
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 29 publications
2
44
1
Order By: Relevance
“…Despite the fact that the HMIS is the backbone for strong health systems, studies in Sub-Saharan Africa (SSA) have reported challenges with data quality, including completeness and timeliness, accuracy, consistence and poor utilization of HMIS tools [1,[5][6][7][8][9][10][11][12][13]. The concerns about the quality of routine information have undermined data utilization for decision-making in the health sector [9,10,[14][15][16][17][18][19][20]. Completeness and timeliness entails completeness of reports, completeness of data and timeliness of reports; while consistency refers to accuracy, outliers, trends and consistency between indicators.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that the HMIS is the backbone for strong health systems, studies in Sub-Saharan Africa (SSA) have reported challenges with data quality, including completeness and timeliness, accuracy, consistence and poor utilization of HMIS tools [1,[5][6][7][8][9][10][11][12][13]. The concerns about the quality of routine information have undermined data utilization for decision-making in the health sector [9,10,[14][15][16][17][18][19][20]. Completeness and timeliness entails completeness of reports, completeness of data and timeliness of reports; while consistency refers to accuracy, outliers, trends and consistency between indicators.…”
mentioning
confidence: 99%
“…Another study in Nigeria, reported that facility-reported data were incomplete by 40% of the time [18]. On the other hand, internal data inconsistency is quite common in a number of countries in Sub-Saharan Africa [18,19,21]. Both underand over-reporting have been frequently observed, and it varied across indicators, facilities and districts [18,22].…”
mentioning
confidence: 99%
“…Another study in Nigeria, reported that facility-reported data were incomplete by 40% of the time [18]. On the other hand, internal data inconsistency is quite common in a number of countries in Sub-Saharan Africa [18][19]21]. Both under-and overreporting have been frequently reported, and it varied across indicators, facilities and districts [18,22].…”
Section: Introductionmentioning
confidence: 99%
“…Both under-and overreporting have been frequently reported, and it varied across indicators, facilities and districts [18,22]. For instance, in a study in Rwanda, over-reporting was observed for ante-natal care-related data than for other indicators [19]. In some cases, missing values, measurement error, inaccuracy and false reports from unidenti ed source have been observed [20].…”
Section: Introductionmentioning
confidence: 99%
“…Another study in Nigeria, reported that facility-reported data were incomplete by 40% of the time [18]. On the other hand, internal data inconsistency is quite common in a number of countries in Sub-Saharan Africa [18][19]21]. Both under-and overreporting have been frequently observed, and it varied across indicators, facilities and districts [18,22].…”
Section: Introductionmentioning
confidence: 99%